The impact of tobacco taxes on mortality in the USA, 1970–2005. Issue 1 (28th October 2014) - Bowser, Diana; Canning, David; Okunogbe, Adeyemi
Abstract : Objectives: This paper aimed to estimate the effect of tobacco taxes on total mortality and cause-specific mortality in the 50 States plus the District of Columbia, USA, over the period 1970–2005 as well as the net effect on deaths averted in 2010. Methods: We used a fixed effects panel regression to measure the impact of changes in total tobacco taxes on total and cause-specific mortality rates over the period 1970–2005, using a 5-year lag structure between changes in tobacco taxes and mortality rates. The estimates were used to determine the number of deaths averted in the year 2010 by tobacco tax increases over the period 1970–2005. Results: Descriptive results showed that nominal total tobacco tax increased from US0.18 in 1970 to US1.24 in 2005, which after adjusting to 2005 US, corresponds to an increase in real total tobacco tax from US 0.89 in 1970 to US 1.24 in 2005. We found that increases in total tobacco tax were beneficial, with a 1 increase in total tobacco tax decreasing overall mortality rate by 8.0%. Based on these results, we estimated a net saving of 53 300 lives in 2010 due to the tobacco tax changes over the period 1970–2005. Conclusions: Our results demonstrate that higher tobacco taxes lead to lower total mortality rates and avoided deaths. Strong tobacco tax policies are essential to improving overall population health.